2018
DOI: 10.1017/s0714980818000557
|View full text |Cite
|
Sign up to set email alerts
|

Considering Age-Related Hearing Loss in Neuropsychological Practice: Findings from a Feasibility Study

Abstract: RÉSUMÉLa perte auditive représente une problématique répandue chez la population âgée. Cela peut poser des défis pour les neuropsychologues, étant donné que les méthodes d’intervention doivent être présentées oralement et donc entendues avec précision. Dans cette étude, le statut auditif de 20 clients (âge moyen= 71 ans) a été évalué au sein d’une clinique de neuropsychologie en milieu hospitalier et l’impact de cette évaluation sur la pratique des neuropsychologues a été étudié. Un assistant de recherche a ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Consistent with their findings, Dupuis et al (2015) found that older adults with hearing loss had poorer recall of visually presented words than those with normal hearing and that environmental testing conditions (e.g., noise) affected test results, especially for older adult with clinically significant pure-tone hearing loss, but also including those who had clinically normal audiometric thresholds (Dupuis et al, 2016). These kinds of findings have important implications for the potential mechanisms underlying the associations as well as for clinical best practices (Dupuis et al, 2019).…”
Section: Sensory Status and Cognitive Performancementioning
confidence: 99%
“…Consistent with their findings, Dupuis et al (2015) found that older adults with hearing loss had poorer recall of visually presented words than those with normal hearing and that environmental testing conditions (e.g., noise) affected test results, especially for older adult with clinically significant pure-tone hearing loss, but also including those who had clinically normal audiometric thresholds (Dupuis et al, 2016). These kinds of findings have important implications for the potential mechanisms underlying the associations as well as for clinical best practices (Dupuis et al, 2019).…”
Section: Sensory Status and Cognitive Performancementioning
confidence: 99%
“…6 Hearing deficits are more prevalent with the aging population. 7,8 Using a telephone, the patient may not hear well the examiners' instructions, and it may be difficult for the examiner to distinguish between the patient's hearing difficulty versus attentional impairment or an external distraction. In an office setting, visual cues could compensate over reduced hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, hearing loss can negatively affect performance on the most frequently used screening tests for cognition, such that tests administered verbally can result in an over-estimation of the presence or level of cognitive impairment when sensory impairments are not considered [ 66, 67 ]. The presence and severity of hearing impairment has not only been found to be under-estimated by the specialists tasked with the assessment and diagnosis of cognitive disorders [ 64, 65 ], but also by the health professionals responsible for the care of older adults living with dementia, many of whom may have multiple comorbidities [ 50 ].…”
Section: Introductionmentioning
confidence: 99%